Digital Entrepreneurship, Gender and Intersectionality An East Asian Perspective - Leung, Wing-Fai (Dynamics of Virtual Work, 2019)
This book details qualitative research focusing on Internet startups, digital entrepreneurship, race and sex discrimination, and the sharing economy. Addressing the intersections between issues of gender, age, ethnicity and class, the author interviews startup founders, including many husband and wife teams, in order to understand the working and private lives of digital entrepreneurs in and from Taiwan who utilise Internet and mobile technologies, against a backdrop of the country's political, social and economic history. It investigates contemporary debates about entrepreneurship as they are experienced by new generations of start-uppers who challenge existing social and cultural norms by becoming creative workers and embracing the precarity that exists in the volatile digital economy.